Fourth Five Year Plan of Madhya Pradesh Mid-Term Appraisal - Planning Commission (Planning Commission)
In the industrial sector, the aim is to develop basic infrastructural facilities in industrial areas and industrial estates. Despite many locational advantages, the State is yet to attract entrepreneurs for establishing huge scale industries. Several concessions have been announced by the State Government to attract entrepreneurs. Measures will be taken to develop the 33 industrially backward districts.
Madhya Pradesh